Evaluasi terhadap Sistem Informasi Akuntansi Penerimaan dan Pengeluaran Kas - Firman Faturahman; Surya, Rendra Trisyanto; Supriatna, Iyeh (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
The goal of this research is to determine and examine whether the existing cash reception and spending accounting information system at PT Mustika Hegar Rekatama in principle conforms with the primary components of the accounting information system. A case study was used in this investigation. Information is gathered through interviews. (1) descriptive analysis; (2) comparing the suitability of PT Mustika Hegar Rekatama's cash receipts and expenditures with the main elements of the accounting information system; and (3) identifying the accounting information system elements for cash receipts and expenditures at PT Mustika Hegar Rekatama. According to the findings of this study, PT Mustika Hegar Rekatama's accounting information system for cash receipts and expenditures has met the primary requirements of an accounting information system.